A revised method of troponin exchange in permeabilised cardiac trabeculae using vanadate: functional consequences of a HCM-causing mutation in troponin I. - Preston, L; Watkins, H; Redwood, C (2006)
In order to incorporate human cardiac troponin I (TnI) and troponin C (TnC) into guinea pig skinned cardiac trabeculae, fibres were treated with vanadate to extract endogenous TnI and TnC using established protocols. After addition of human TnI and TnC force was inadequately restored and it was found that the vanadate treatment had unexpectedly also removed some troponin T. To recover Ca(2+)-sensitive force, the fibres had to be incubated with all three troponin subunits. Using this revised method, the hypertrophic cardiomyopathy-causing mutation TnI Gly203Ser had no significant effect on Ca(2+)-sensitivity of force production, contrasting with our earlier report of decreased Ca(2+)-sensitivity which was likely caused by the unexpectedly harsh effect of vanadate.